Hidden work and the challenges of scalability and sustainability in ambulatory assisted living - Procter, R; Wherton, J; Greenhalgh, T (Association for Computing Machinery, 2018)
Assisted living technologies may help people live independently while also—potentially—reducing health and care costs. But they are notoriously difficult to implement at scale and many devices are abandoned following initial adoption. We report findings from a study of global positioning system (GPS) tracking devices intended to support the independent living of people with cognitive impairment. Our aims were threefold: to understand (through ethnography) such individuals’ lived experience of GPS tracking; to facilitate (through action research) the customization and adaptation of technologies and care services to provide effective, ongoing support; and to explore the possibilities for a co-production methodology that would enable people with cognitive impairment and their families to work with professionals and technical designers to shape these devices and services to meet their particular needs in a sustainable way. We found that the articulation work needed for maintaining the GPS technology in “working order” was extensive and ongoing. This articulation work does not merely supplement formal procedures, a lot of it is needed to get round them, but it is also often invisible and thus its importance goes largely unrecognized. If GPS technologies are to be implemented at scale and sustainably, methods must be found to capitalize on the skills and tacit knowledge held within the care network (professional and lay) to resolve problems, improve device design, devise new service solutions, and foster organizational learning.